Properties of polypropylene/TiO2 nanocomposites: The melt rheology, tensile strength and electrical characteristics - Giang, Nguyen Vu; Huynh, Mai Duc; Trung, Tran Huu (Vietnam Journal of Chemistry, 2012)
Titanium dioxide (TiO2) in rutile crystal form with and without modification by 1 wt% of 3-glycidoxypropyl-trimethoxy silane were mixed with isotactic polypropylene (PP) at 180oC to prepare nanocomposites. Investigation of melt rheology of nanocomposites showed the relative melt viscosity increased with increasing levels of original TiO2 (ORT) and modified TiO2 (MRT). Tensile test of samples revealed that mechanical properties of PP/MRT nanocomposites have significantly improved in comparison with PP/ORT nanocomposites. The maximum value of tensile strength and Young’s modulus of PP/MRT reached 42 MPa and 979 MPa, respectively, at 2 wt% of MRT. The investigation of accelerated weathering test of nanocomposites revealed the retention in tensile strength of PP/ORT and PP/MRT nanocomposites are higher than that of pure PP. The electrical properties of PP/ORT and PP/MRT nanocomposites were also studied. The results showed that both MRT and ORT decreased electric insulation of PP. However, electric insulation of PP/ORT nanocomposites is still higher than that of PP/MRT nanocomposites.